Learning Design Based on Local Wisdom Maddawa-dawa, Mammanu-manu and Mappettuada - F. A, A. Nurannisa; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar (Universitas Muhammadiyah Mataram, 2020)
Local traditions of Maddawa-dawa, Mammanu-manu, Mapppettuada as a form of local wisdom that elaborated entry into learning, especially mathematics. In its application the local traditions of Maddawa-dawa, Mammanu-manu, Mapppettuada integrated with an android application, namely the application of group maker is used on the phase Maddawa-dawa, application lucky wheel and mind mapping is used on the phase Mammanu-manu and application pro & cons used on the phase Mappettuada. This research emphasizes the design process with a focus on the literature review in finding the proper integration between local traditions of Maddawa-dawa, Mammanu-manu, Mapppettuada with android apps that are focused student-centered in learning. The results of this design are expected to provide an alternative solution in improving the ability of extrapolation of the students especially in the learning of mathematics through the approach of local traditions in the learning process.